Effective Control And Correction Of The Main Risk Factors Of Hypertonic Disease In The Conditions Of The Primary Line Of Health Care - Shakhzada S. Gulyamova (International Journal of Medical Sciences And Clinical Research, 2025)
The past 5-year data from 222 randomly selected outpatient cards of hypertensive patients who were followed up at a family polyclinic (n=54) and in a number of rural ambulances (n=168) of the Republic of Uzbekistan were retrospectively analyzed. The physicians from the Tashkent family polyclinic and rural ambulances of a number of the Republic’s regions, who had taken 10-month retraining courses for general practitioners, were questioned. Two hundred and fifty-six hypertensive patients followed up at the family hospital and rural ambulances were interviewed using questionnaires and examined. Then some of them (a study group) took a course of training at a school for the hypertensive patient and the others (a comparison group) did not participate in the education program. All the patients were followed up for 2 years with a subsequent reexamination and study. Most outpatient cards give recommendations for non-drug treatment incompletely. In a number of cases, the physicians who attach importance to the detection and correction of risk factors have substantially increased after education. The patients who had taken training courses were found to be significantly (р<0,001) more aware of their having hypertension and the major risk factors of hypertensive disease, to be more adherent to treatment, and to know its adequacy.